Trinidad - (:unkn) unknown (My University, 2011)
This postcard bears two lithographs, one of the city of Port of Spain, the capital of Trinidad and the other the Government House.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Historic sites; Cities and towns--Port of Spain; 1901; Government House; Botanical gardens; Public buildings